One deadly eye ebook - Wayne White, Randy (Doc Ford, 2024)
*NATIONAL BESTSELLER* From New York Times bestselling author Randy Wayne White, after the deadliest hurricane to hit Florida's Gulf Coast in a century, Doc Ford must stop a gang of thieves — and worse — during the twelve hours of chaos that follow the passing of a storm's eye. A Russian diplomat disappears while Doc is tagging great white sharks in South Africa, and members of a criminal brotherhood, Bratva, don't think it's a coincidence. They track the biologist to Dinkin's Bay Marina on the west coast of Florida, where Brotherhood mercenaries have already deployed, prepared to pillage and kill in the wake of an approaching hurricane. No one, however, is prepared for a cataclysmic event that will forever change the island and leaves Doc to deal with escapees from Russia's most dangerous prison, including a serial killer—the Vulture Monk—who has a taste for blood. His only ally is an enigmatic British inventor whose decision to ride out the storm might have more to do with revenge than protecting a priceless art collection. Doc has a lot at stake—the lives of his fiancée, Hannah Smith, and their son, plus the fate of his hipster pal, Tomlinson, whose sailboat has disappeared in the Gulf of Mexico. The greatest threat of all, though, is a force that cannot be escaped—a Category Five hurricane that, minute by minute, melds sins of the past with Florida's precarious future.